Effects of high intensity training on specific performance related parameters in young female basketball players - Sperlich, P. F.; Zinner, C.; Mester, J. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Basketball is an intermittent high- intensity team sport, which emphasizes the anaerobic and aerobic energy system. The ability to recover from high intensity activities is limited by the individual`s aerobic capacity. Different high intensity training (HIT) protocols have been shown to improve aerobic capacity in male soccer and basketball players (Delextrat and Martinez, 2013; Sperlich et al., 2011; Helgerud et al., 2001). The purpose of this study was to investigate the effect of a 5- week in- season, HIT on aerobic fitness, sprinting and jumping ability, in female elite Basketball players. Methods: 25 female 1st national youth division basketball players (age: 15.1 ± 1.1 yrs, height: 170 ± 5.1 cm, body mass: 60.8 ± 5.9 kg, mean ± SD) took part in the study. 11 subjects integrated a 5-week HIT in their team training while 14 served as controls and continued their common team- training routine. Two different basketball specific HIT- sessions were conducted twice a week on nonconsecutive days. A long interval session (4 x 4-min, 3 min rest) was conducted 7 times and every third session consisted of short intervals (2 sets of 15 x 30s with 15s rest, 3 min rest in between sets). Before and after the 5-week training intervention, players` fitness was tested through sprint (with and without ball), vertical jump (CMJ, CMJ with arm swing, SJ) and the Yo-Yo intermittent recovery test Level 1 (Yo-Yo IR 1). Results: No significant changes were observed for either group in the vertical jump tests or both sprint tests. However the Yo-Yo IR 1 performance increased significantly in the HIT group, with no changes in the control group (pre: 1498.2±266.2m; post: 1894.6±421.2m; p = 0.0042). Discussion: The HIT sessions did not involve special power related tasks, therefore the sprint and vertical jump performance remained unchanged. However the HIT did not show any negative effect on these values. Previously published studies suggested, either a 4x4 min protocol (Helgerud et al. 2001), a mix of various types of HIT sessions (Sperlich et al. 2013) or a protocol of shorter intervals would improve the aerobic fitness of male elite basketball players (Delextrat and Martinez, 2013). Based on our findings, an in- season HIT program, with short and long intervals, can be conducted to improve aerobic capacity in elite female players